Steroids from the red alga Acanthophora spicifera - Lang, Karen L. (2007)
The alga Acanthophora spicifera (Vahl) Borgesen (Ceramiales: Rhodophyta) is a rhodophycean alga with wide distribution throughout the tropics and subtropics (Kilar and McLachlan, 1986) and one of the most abundant red algal species found on reef flats (Joikel and Morrissey, 1986). Investigation with this species is rather scarce (Aihara and Yamamoto, 1968; Wahidulla et al., 1986, 1991, 1998; Wahidulla and Kamat, 1991; Prakash et al., 1989; Wang et al., 1998, 2003). Therefore, as a part of the systematic chemical research with rhodophycean algae, we report here the results concerning the main sterols isolated from A. spicifera, an abundant alga in Southern Brazil.